POSSIBILITIES AND ADVANTAGES OF USING STEAM TECHNOLOGIES IN TEACHING FOREIGN (ENGLISH) LANGUAGE TO STUDENTS OF MINING AND METALLURGY - Sharipova Iroda Azamatovna (Scholars Digest Publishing, 2023)
The article is devoted to the peculiarities of the formation of lexical skills. Different principles, methods and approaches to teaching vocabulary are considered. The concept of developing professional lexical competence of mining and metallurgical students on the basis of modern technologies of education, first of all, teaching based on an integrative approach connecting various disciplines, today presents many tasks to the specialist working in this field. Because interrelated teaching of subjects requires not only mastering the subject, but also the ability to pass the content of the subject in English and use it in practice. Therefore, it is one of the urgent issues that a specialist working in the field should emphasize the use of interrelated subjects in teaching, that is, the improvement of interdisciplinary communication.
Keywords: vocabulary, lexical skill, lexical unit, unit of speech, somatization, STEAM, foreign language, teaching approaches.